Pengembangan Film Animasi 3D “Hitam Kucingmu Putih Kucingku” - Sihabul Milah; Riwinoto Riwinoto (JURNAL INTEGRASI, 2014)
3D animation film "Hitam Kucingmu Putih Kucing" was developed with the aim of conveying a message of peace to children of primary school age. As multimedia application, this animation film is developed with multimedia development methodology Luther-Sutopo. The concept of 3D digital animation film is a two minutes film with rotoscope animation style. The film was designed by film’s design tools : synopsis, plot, outline, scenarios and storyboards. In collecting material obtained 16 3D models, 3 images, 5 audio s, and 3 musics as material for processing into animated films throughout 3,638 frames. The test results for children in a housing in Batam showed that visual animated film was rated good and the message is quite acceptable.